Association of Adverse Pregnancy Outcomes With Hypertension 2 to 7 Years Postpartum. Issue 19 (1st October 2019) - Haas, David M.; Parker, Corette B.; Marsh, Derek J.; Grobman, William A.; Ehrenthal, Deborah B.; Greenland, Philip; Bairey Merz, C. Noel; Pemberton, Victoria L.; Silver, Robert M.; Barnes, Shannon; McNeil, Rebecca B.; Cleary, Kirsten; et al.
Abstract : Background: Identifying pregnancy‐associated risk factors before the development of major cardiovascular disease events could provide opportunities for prevention. The objective of this study was to determine the association between outcomes in first pregnancies and subsequent cardiovascular health. Methods and Results: The Nulliparous Pregnancy Outcomes Study Monitoring Mothers‐to‐be Heart Health Study is a prospective observational cohort that followed 4484 women 2 to 7 years (mean 3.2 years) after their first pregnancy. Adverse pregnancy outcomes (defined as hypertensive disorders of pregnancy, small‐for‐gestational‐age birth, preterm birth, and stillbirth) were identified prospectively in 1017 of the women (22.7%) during this pregnancy. The primary outcome was incident hypertension (HTN). Women without adverse pregnancy outcomes served as controls. Risk ratios (RR) and 95% CIs were adjusted for age, smoking, body mass index, insurance type, and race/ethnicity at enrollment during pregnancy. The overall incidence of HTN was 5.4% (95% CI 4.7% to 6.1%). Women with adverse pregnancy outcomes had higher adjusted risk of HTN at follow‐up compared with controls (RR 2.4, 95% CI 1.8‐3.1). The association held for individual adverse pregnancy outcomes: any hypertensive disorders of pregnancy (RR 2.7, 95% CI 2.0‐3.6), preeclampsia (RR 2.8, 95% CI 2.0‐4.0), and preterm birth (RR 2.7, 95% CI 1.9‐3.8). Women who had an indicated preterm birth and hypertensive disorders of pregnancy had the highest risk of HTN (RR 4.3, 95% CI 2.7‐6.7). Conclusions: Several pregnancy complications in the first pregnancy are associated with development of HTN 2 to 7 years later. Preventive care for women should include a detailed pregnancy history to aid in counseling about HTN risk. Clinical Trial Registration: URL: http://www.clinicaltrials.gov Unique identifier: NCT02231398.